Pattern of Gallbladder Diseases in an Academic Hospital - Two Years Study - Hossian, Nabir; Parvin, Saila; Ali, Ahammed; Akhter, Jaheeda; Habib, AKM Kaswar; Hossain, Sanwar; Haque, Abdul Hasnat Md. Afzalul (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 204-208 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15359